Neko Nursery & Cafe / Nur Farah Syakila Sharun ... [et al.] - Sharun, Nur Farah Syakila; Jordan, Nur Sarah Maria; Marali, Nur Asyiqin; Ismail, Nur Syuhada; Japar, Rozaimah (2015)
We have discussed and built a partnership to start our own business. The name of our business is called 'Neko Nursery & Cafe'. The main objective of our business is to make our Neko Nursery & Cafe proceed smoothly by following the business plan which consists of administration, operational, marketing and financial planning. Each of the planning has their own professional manager on their task and responsibilities. Our business will mainly focus on providing services for cats and serving a wide variety of refreshing foods and beverages. Within our business, we have also appointed managers to operate m different departments which are authoritative so that our business can operate smoothly. These departments are Administrative Manager, Marketing Manager, Operation Manager and Financial Manager. These managers will control each of the department while there will be one person acts as General Manager, who will be the head of all the departments in our business. Our office is situated in our cafe so that it will be easy for us to access while operating the business. It is located in block 4, No 56, Jalan Alamesra, Sepanggar, Kota Kinabalu, Sabah. We choose this location because it is located near !Borneo where numerous educational institutions, offices and residential areas are present. So, we decided to grab the chance by operating our business at that location in order to attract and introduce our product to our potential target market.